2010
DOI: 10.1186/1758-907x-1-7
|View full text |Cite
|
Sign up to set email alerts
|

microRNA as a new immune-regulatory agent in breast milk

Abstract: BackgroundBreast milk is a complex liquid that provides nutrition to the infant and facilitates the maturation of the infant's immune system. Recent studies indicated that microRNA (miRNA) exists in human body fluid. Because miRNAs are known to regulate various immune systems, we hypothesized that human breast milk contains miRNAs that may be important for the development of the infant's immune system.FindingsWe profiled miRNA expression in human breast milk and detected high expression levels of immune-relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

35
497
1
8

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 478 publications
(541 citation statements)
references
References 24 publications
35
497
1
8
Order By: Relevance
“…We speculated that isolated mEVs can be used for various applications. Human-milk-derived mEVs have been shown to modulate the functionality of immune cells [12,31]. Similar to human mEVs, bovine mEVs may have a biological function, as described previously [16].…”
Section: Resultsmentioning
confidence: 92%
“…We speculated that isolated mEVs can be used for various applications. Human-milk-derived mEVs have been shown to modulate the functionality of immune cells [12,31]. Similar to human mEVs, bovine mEVs may have a biological function, as described previously [16].…”
Section: Resultsmentioning
confidence: 92%
“…Studies conducted by several research groups have confirmed the presence of miRNAs in various body fluids in humans, including serum [49][50][51], plasma [49,50], saliva [52], urine [53], milk [54], cerebrospinal fluid [55] and seminal fluid [56]. In cancer, there is a distinct relationship between the type of biological material and the original location of the neoplasm (e.g.…”
Section: Extracellular Mirnamentioning
confidence: 99%
“…MicroRNAs milk derivatives are stable under harsh conditions such as freeze-thaw cycles and low pH (pH 1); this is of importance for premature newborns, VLBW, and hospitalized infants, who usually receive freezer-stored breast milk (even donated). Low pH stability suggests that miRNAs can be tolerated by newborn's gastrointestinal milieu and could be absorbed into the small intestine directly influencing the gut mucosal immunity and therefore microbiome (11,67). The analysis of miRNAs profile, in human breast milk, with respect to innate immunity could represent a strategy to treat critical premature newborns.…”
Section: Nutrition: the Role Of Micrornasmentioning
confidence: 99%